An efficient physically-based damage model for interface damage of composites sleeved interference joint and influence analysis of its interface friction. (1st November 2021) - Xu, Guanhua; Zhang, Kaifu; Cheng, Hui; Luo, Bin; Zou, Peng; Liang, Biao
Abstract: Interface damage caused by the installation process accelerates damage initiation and evolution of composites joint during service. Accurate prediction of interface damage in the installation is crucial for the reliable application of composites joint. A physically-based 3D anisotropic progressive model was developed for predicting the interface damage of composites sleeved interference joint in the installation. The model employed the physically-based failure criteria considering in-situ strength effects and fiber kinking to characterize damage initiation. A cost-effective algorithm that quickly searches for the maximum fracture angle on the critical fracture plane was adopted to improve the calculation efficiency. Installation process simulations were conducted and validated with experiments. The influence of interface friction coefficient on the press-in load and interface damage were analyzed. Results show that the press-in load in the installation process is primarily dependent on the interface friction of bolt-sleeve interface. To alleviate the interface damage, aside from keeping the friction coefficient of bolt-sleeve interface with small value, choosing an appropriate friction coefficient of sleeve-CFRP interface is also very important.